2011
DOI: 10.1152/ajpgi.00281.2010
|View full text |Cite
|
Sign up to set email alerts
|

The nutriceutical bovine colostrum truncates the increase in gut permeability caused by heavy exercise in athletes

Abstract: Heavy exercise causes gut symptoms and, in extreme cases, "heat stroke" partially due to increased intestinal permeability of luminal toxins. We examined bovine colostrum, a natural source of growth factors, as a potential moderator of such effects. Twelve volunteers completed a double-blind, placebo-controlled, crossover protocol (14 days colostrum/placebo) prior to standardized exercise. Gut permeability utilized 5 h urinary lactulose-to-rhamnose ratios. In vitro studies (T84, HT29, NCM460 human colon cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
163
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(181 citation statements)
references
References 24 publications
14
163
2
2
Order By: Relevance
“…Supplementation with bovine colostrum has been shown to be beneficial in maintaining intestinal integrity. For example, Marchbank et al [8] conducted a placebo-controlled, counterbalanced crossover study to determine the effects of bovine colostrum supplementation on exercise-induced changes in intestinal permeability. Subjects were required to run on a treadmill for 20 minutes (which caused core body temperature to increase by between 1 and 2°C) after 2 weeks of daily supplementation with 20 g per day of bovine colostrum or a protein and energy-matched placebo.…”
Section: Bovine Colostrum Supplementation and Intestinal Barrier Intementioning
confidence: 99%
See 1 more Smart Citation
“…Supplementation with bovine colostrum has been shown to be beneficial in maintaining intestinal integrity. For example, Marchbank et al [8] conducted a placebo-controlled, counterbalanced crossover study to determine the effects of bovine colostrum supplementation on exercise-induced changes in intestinal permeability. Subjects were required to run on a treadmill for 20 minutes (which caused core body temperature to increase by between 1 and 2°C) after 2 weeks of daily supplementation with 20 g per day of bovine colostrum or a protein and energy-matched placebo.…”
Section: Bovine Colostrum Supplementation and Intestinal Barrier Intementioning
confidence: 99%
“…The observed a reduction of heat-induced apoptosis in these cells, was shown to be partly attributed to epidermal growth factor (EGF) present in the colostrum, confirmed by incubation with anti-EGF antibodies, although some of the anti-apoptotic processes were unaltered by anti-EGF, showing that other factors must also contribute. Marchbank et al [8] also showed that bovine colostrum enhanced heat shock proteins (HSPs) induction under basal and heat stress conditions. This is another possible mechanism to explain the beneficial effects of colostrum as HSPs provide cellular protection against numerous insults, including heat and oxidative stresses, and it is likely that this also contributed to the truncated exercise-induced rise in intestinal permeability seen in this study.…”
Section: Used In Vitro Investigations Withmentioning
confidence: 99%
“…Recent research has also shown that 14 days of supplementation with bovine colostrum can reduce the increase in gut permeability after acute, vigorous exercise possibly by mechanisms including reducing temperature-induced apoptosis ( Marchbank et al, 2011). Although research is limited, this study suggests that colostrum supplementation may be benefi cial in maintaining gut stability during exercise and could help prevent GI discomfort.…”
Section: Management Of Gi Symptomsmentioning
confidence: 69%
“…These molecules undergo active carrier-mediated, passive carrier-mediated, transcellular and paracellular transport, respectively, in the small intestine. They are widely used as diagnostic tools to detect disturbances in these processes [15,16]. It is believed that the most representative parameter of intestinal wall integrity is the L/R ratio, which is normally below 0.05 [17].…”
Section: Discussionmentioning
confidence: 99%